Finite Element Simulation of Aluminium/GFRP Fibre Metal Laminate under Tensile Loading - M. N. M., Merzuki; M. R. M., Rejab; Bachtiar, Dandi; Siregar, J. P.; M. F., Rani; Salwani, Mohd Salleh (IOP Publishing, 2018)
The response of a fibre metal laminate (FML) model to the tensile loading is predicted through a computational approach. The FML consisted with layers of aluminum alloy and embedded with one layer of composite material, Glass fibre Reinforced Plastic (GFRP). The glass fibre and aluminium alloy 2024-0 was laminated by using thermoset epoxy. A compression moulding technique was used in the process of a FML fabrication. The aluminium has been roughen by a metal sanding method which to improve the bonding between the fibre and metal layer. The main objective of this paper is to determine the failure behaviour of the FML under the tensile loading. The responses on the FML under the tensile loading were numerically performed. The FML was modelled and analysed by using Abaqus/CAE 6.13 version. Based on the experimental and FE data of the tensile, the ultimate tensile stress is 120 MPa where delamination and fibre breakage happened. A numerical model was developed and agreed well with the experimental results. The laminate has an inelastic respond to increase the tensile loads which due to the plasticity of the aluminium layers.